Farmer boy ebook - Wilder, Laura Ingalls (Little House, 2016)
The second book in Laura Ingalls Wilder's treasured Little House series—now available as an ebook! This digital version features Garth Williams's classic illustrations, which appear in vibrant full color on a full-color device and in rich black-and-white on all other devices. While Laura Ingalls grows up on the prairie, Almanzo Wilder is living on a big farm in New York State. Here Almanzo and his brother and sisters help with the summer planting and fall harvest. In winter there is wood to be chopped and great slabs of ice to be cut from the river and stored. Time for fun comes when the jolly tin peddler visits, or best of all, when the fair comes to town. Almanzo wishes for just one thing—his very own horse—and he must prove that he is ready for such a big responsibility. Farmer Boy is Laura Ingalls Wilder's beloved story of how her husband, Almanzo, grew up as a farmer boy far from the little house where Laura lived. The nine Little House books have been cherished by generations of readers as both a unique glimpse into America's frontier history and as heartwarming, unforgettable stories.